2017
DOI: 10.1097/md.0000000000006065
|View full text |Cite
|
Sign up to set email alerts
|

ADMA predicts major adverse renal events in patients with mild renal impairment and/or diabetes mellitus undergoing coronary angiography

Abstract: Asymmetric dimethylarginine (ADMA) is a competitive inhibitor of the nitric oxide (NO)-synthase and a biomarker of endothelial dysfunction (ED). ED plays an important role in the pathogenesis of contrast-induced nephropathy (CIN). The aim of our study was to evaluate serum ADMA concentration as a biomarker of an acute renal damage during the follow-up of 90 days after contrast medium (CM) application.Blood samples were obtained from 330 consecutive patients with diabetes mellitus or mild renal impairment immed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…Alternatively, compounds that inactivate or alter the normal precursor/product ratio have been highlighted: one of these is asymmetric dimethyl arginine (ADMA). It has recently been found that, in type 2 diabetes, ADMA increases significantly after ingestion of a fatty meal, and its levels correlate with the reduction of flow-mediated vasodilatation [ 34 ]. Regarding the second hypothesis, it has been shown that some factors are able to reduce the expression of NOS.…”
Section: Endothelial Dysfunction and Diabetesmentioning
confidence: 99%
“…Alternatively, compounds that inactivate or alter the normal precursor/product ratio have been highlighted: one of these is asymmetric dimethyl arginine (ADMA). It has recently been found that, in type 2 diabetes, ADMA increases significantly after ingestion of a fatty meal, and its levels correlate with the reduction of flow-mediated vasodilatation [ 34 ]. Regarding the second hypothesis, it has been shown that some factors are able to reduce the expression of NOS.…”
Section: Endothelial Dysfunction and Diabetesmentioning
confidence: 99%
“…128,129 Several studies described ADMA and SDMA to be connected to kidney impairment, 130 as well as to the progression of CKD. [131][132][133][134][135][136][137][138][139][140] Recent data identified SDMA within HDL particles of CKD patients but not in healthy controls, and SDMA was considered to be the culprit that modifies HDL and reverts the endothelial-protective properties. This modified HDL induces endothelial dysfunction, impairs endothelial repair, increases BP, and activates endothelial TLR-2 signaling, resulting in enhanced reactive oxygen species production and inhibition of endothelial NO bioavailability.…”
Section: Apo L1mentioning
confidence: 99%
“…Therefore, CIN has become a common complication of PCI, and has become the third leading cause of acute renal failure in hospital. [ 2 , 3 ] The diagnostic criteria of CIN was that the absolute value of serum creatinine (Scr) in 48 to 72 hours after the injection of contrast agent was increased by >44.2 mmol/L or above the base value of 25%, and was not associated with other renal damage. [ 4 , 5 ] In addition to hydration, there is still no effective prophylactic regimen available to prevent occurrence of CIN recently.…”
Section: Introductionmentioning
confidence: 99%